Expected returns and idiosyncratic risk: Industry-level evidence from Russia - Jyri Kinnunen; Minna Martikainen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​In this paper, we explore a relation between expected returns and idiosyncratic risk. As in many emerging markets, investors in the Russian stock market cannot fully diversify their portfolios due to transaction costs, information gathering and processing costs, and short-comings in investor protection. This implies that investors demand a premium for idiosyncratic risk – unique asset-specific risk plays a role in investment decisions. We estimate the price of idiosyncratic risk using MIDAS regressions and a cross-section of Russian industry portfolios. We find that idiosyncratic risk commands an economically and statistically significant risk premium. The results remain unaffected after controlling for global pricing factors and short-term return reversal.
URN:NBN:fi:bof-201511231444
Keywords: G12; 330